Do Social Bonds Buffer the Impact of Adverse Childhood Experiences on Reoffending?. (January 2017) - Craig, Jessica M.; Baglivio, Michael T.; Wolff, Kevin T.; Piquero, Alex R.; Epps, Nathan
Research from multiple disciplines has reported that exposure to childhood traumatic events, often referred to as adverse childhood experiences (ACEs), increases an individual's chances of experiencing a wide variety of negative consequences such as chronic disease, unemployment, and involvement in serious, violent, and chronic offending. The current study assesses how protective factors from social bonds may moderate the relationship between ACEs and future offending in a sample of high-risk adjudicated youth. While results showed that increased ACE exposure led to a higher likelihood of rearrest and more social bonds lowered the likelihood of rearrest, in contrast to expectations, the analyses revealed that stronger social bonds did not reduce the deleterious effects of exposure to more types of ACEs on recidivism. A discussion of these findings is offered, along with study limitations and future directions.